Trends in the utilization of psychotropic medications in China from 2018 to 2021 - Zhang, Xinyan; Hu, Xiaowen; Zhao, Yuxuan; Lu, Christine Y.; Nie, Xiaoyan; Shi, Luwen (Frontiers in Pharmacology, 2022)
Background:Monitoring psychotropic medicine consumption trends can provide information on the extent of pharmacological interventions for mental disorders and availability of psychotropic medicines. Objectives:This study aimed to illustrate the trends in psychotropic drug utilization in China’s hospitals. Methods:We retrospectively analyzed the aggregated monthly psychotropic procurement records of 1009 hospitals from 31 provinces in China from January 2018 to September 2021. Total psychotropic medicine consumption included the sales of antipsychotics, antidepressants, anxiolytics, mood stabilizers, and sedatives or hypnotics. Information, including generic name, procurement amount, dosage form, strength, purchase time, and geographical data, was collected. Population-weighted psychotropic utilization was expressed in defined daily dose per 1000 inhabitants per day (DDD/1000/day). Results:Psychotropic medicine sales increased from 4.5 DDD/1000/day in Q1 2018 to 6.4 DDD/1000/day in Q3 2021; total utilization in China’s hospitals increased by 42.2%. The use of each class of psychotropics showed a gradually increasing trend. Antidepressants were the most consumed psychotropics, accounting for 48.4% of the total psychotropic utilization(3.1/6.4 DDD/1000/day), followed by sedatives or hypnotics(31.3%; 2.0/6.4 DDD/1000/day) and antipsychotics(15.6%; 1.0 /6.7 DDD/1000/day).Among all sub-classes of psychotropics, a most significant growth in DDD per 1000 inhabitants per day was seen for selective serotonin reuptake inhibitors(1.2 to 1.9 DDD/1000/day),whereas the consumption of typical antipsychotics(from 0.1 to 0.09) and tricyclic antidepressants(from 0.05 to 0.03) decreased during the study period.Psychotropic utilization substantially increased between Q1 2018 and Q3 2021 in regions with different economic levels.In Q3 2021,total antibiotic utilization in secondary and tertiary hospitals was 9.4 DDD/1000/day and 6.0 DDD/1000/day,respectively.Sedatives or hypnotics in secondary hospitals accounted for the largest proportion of utilized psychotropics(43.6%; 4.1/9.4 DDD/1000/day),whereas antidepressants were the most commonly used psychotropic in tertiary hospitals(50.0%,3.0/6.0 DDD/1000/day). Conclusion:This study showed that despite increases in psychotropic medication use,the consumption of medicines is still much lower than in other countries and regions internationally. With reference to the estimated prevalence of corresponding mental disorders,our study illustrates that a large treatment gap for mental health problems exists in China.In addition,the wide use of psychotropics with weak clinical evidence raises serious concerns regarding rational use.Greater efforts are needed to increase the availability of psychotropic medicines and to facilitate proper psychotropic use.